PREGNANT ADOLESCENT AND HER FEELINGS ABOUT FAMILY SUPPORT - Giovana de Pires Nunes; Francielle Garcia Sena; Carolina Coutinho Costa; Nalú Pereira da Costa Kerber; Mariza Zanchi; Carla Vitola Gonçalves (Universidade Federal de Santa Maria, 2018)
Aim: to identify the feeling about the main sources of support for young women who have already experienced adolescent pregnancy. Method: qualitative, exploratory and descriptive study, developed in a city in Southern Brazil. The participants were women aged from 10 to 19 years old, who had a child in 2010, excluding those with fetal death, not residing in the municipality or not responsible for the child's raising. Individual interview was carried and the content analysis was used, constituting the categories: relationship between marital status and paternal support and relationship between the family reaction to gestation and the support received. Results: the participation and support of the babies' parents and the maternal figure in the context of teenage pregnancy seem essential to face the situation of becoming a mother. Conclusion: understanding the way that adolescents feel the support when facing a pregnancy, at such stage of their lives, may contribute to the public policies and work processes directed to their needs.